The Art of Publlic Speaking - Stephen E. Lucas (McGraw-Hill, 2004)
Terdiri dari 4 eksemplar dengan 8 CD, Besar file CD 1: 552 MB, CD 2: 512 MB, Durasi CD 1 : 54;81, CD 2 : 01;33;05, berisi : getting started, Basic features of the CD-Rom 4.0, The Audio Abridgement CDs, Videos (Disk 1 and 2), Study Questions, Notepad, Key-Term Flashcards, Speech Preparation Checklists, Speech Outliner, Outline Exercise, Bibliography Formats, Bibliomaker, Online Learning Center, Questionnaire Mker for Audience Analysis Questionnaires, Top 100 American Speeches of the 20th Century, Public Speaking PowerWeb, Using the CD-ROM 4.0 and the Audio Abridgement CDs Outside the Classroom, Using the CD-ROM 4.0 to Reduce Speech Anxiety, Using the CD-ROM 4.0 to Improve Speech delivery, Using the CD-ROM 4.0 to Organize and Outline a Speech, Using the CD-ROM 4.0 to Develop Critical Thinking Skills,Using the CD-ROM 4.0 and the Audio Abridgement CDs to prepare for Test, Technical Support. Judul dalam kemasan.